Formation of Annual Ring Eccentricity in Coarse Roots within the Root Cage of Pinus ponderosa Growing on Slopes - Montagnoli, Antonio (Plants (Basel), 2020)
The coarse roots of Pinus ponderosa included in the cage are the ones most involved in tree stability. This study explored the variations in traits, such as volume, cross-sectional area, and radius length of cage roots, and used those data to develop a mathematical model to better understand the type of forces occurring for each shallow lateral root segment belonging to different quadrants of the three-dimensional (3D) root system architecture. The pattern and intensity of these forces were modelled along the root segment from the branching point to the cage edge. Data of root cage volume in the upper 30 cm of soil showed a higher value in the downslope and windward quadrant while, at a deeper soil depth (>30 cm), we found higher values in both upslope and leeward quadrants. The analysis of radius length and the cross-sectional area of the shallow lateral roots revealed the presence of a considerable degree of eccentricity of the annual rings at the branching point and at the cage edge. This eccentricity is due to the formation of compression wood, and the eccentricity changes from the top portion at the branching point to the bottom portion at the cage edge, which we hypothesize may be a response to the variation in mechanical forces occurring in the various zones of the cage. This hypothesis is supported by a mathematical model that shows how the pattern and intensity of different types of mechanical forces are present within the various quadrants of the same root system from the taproot to the cage edge.